Comparison of Nonphaco small incision Cataract Surgery with Conventional Method: An Observational Study - Sultana, Shamima; Sharif, AQM Omar; Begum, Nazneen; Parveen, Salma; Begum, Wahida; Haque, MM Ehsanul (Journal of National Institute of Neurosciences Bangladesh, 2019)
Background: Cataract surgery is very important for the correction of visual acuity among the patients. Objective: The purpose of the present study was to assess the uncorrected visual acuity in small incision cataract surgery (SICS) with PCIOL than conventional method of ECCE with PCIOL implantation. Methodology: This cross-sectional study was conducted at National Institute of Ophthalmology, Dhaka, Bangladesh from January 1999 to December 2000 for a period of two (02) years. Patients with senile cataract were selected for study. A comparative study of changes in postoperative visual outcome and refractive status during post-operative follow up period up to 2 months were observed and documented between two groups of patients, one with suture less nonphaco SICS with PCIOL another with conventional ECCE with PCIOL. All the cataract surgery were done by the same surgeon, and in same place. All the patients were examined carefully both pre and post-operatively. For the purpose of recording, a proforma was made that includes particulars of the patient, complete history, general examination, ocular examination, relevant investigations, operation note, perioperative complications, post-operative follow-up, pre and post-operative visual acuity with keratometric reading. Result: A total of 60 eyes of cataract patients were included in the study of which 30 eyes of cataract patients were randomly selected for suture less nonphaco SICS with PCIOL and 30 eyes of cataract patients were for conventional ECCE with PCIOL.Mean age distribution (58.83±5.55 and 58.77±6.56) was similar in both groups. The unaided vision in both SICS & ECCE group at different postoperative intervals was reported. At day7 and month 1 postoperatively the result appears highly significant between the two groups. At day 1 and month 2 also shows the significant result between the 2 groups. The best corrected visual acuity in SICS and ECCE group at different postoperative intervals was measured. At day 7 and month 1 postoperatively the result appears highly significant between the two groups. At day 1 and month 2 also shows the significant result between the 2 groups.In SICS group out of 30 patients, 7(23.3%) cases acquired unaided vision 6/9 at day 1, 10(33.3%) patients at day 7,14(46.6%)patients at month 1 and 15(49.9%) patients at month 2. On the other hand in ECCE group no patient was found with vision ≥6/9 at day 1 and only one patient with vision ≥6/9 at day 7.At month 1 there were 5(16.6%) patients, and at month 2 there were 9(29.9%)patients with vision ≥6/9. Nearly 50.0% patients of SICS group achieve unaided vision of ≥6/9 within the follow up period of 02 months. Conclusion: In conclusion Uncorrected visual acuity in SICS cases were better than that of ECCE cases with sutures. Journal of National Institute of Neurosciences Bangladesh, 2019;5(2): 185-190